2016
DOI: 10.1016/j.ram.2016.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Patogenicidad de especies de Fusarium asociadas a la pudrición basal del ajo en el centro norte de México

Abstract: Garlic in Mexico is one of the most profitable vegetable crops, grown in almost 5,451ha; out of which more than 83% are located in Zacatecas, Guanajuato, Sonora, Puebla, Baja California and Aguascalientes. Blossom-end rot caused by Fusarium spp is widely distributed worldwide and has been a limiting factor in onion and garlic production regions, not only in Mexico but also in other countries. The presence of Fusarium oxysporum has been reported in Guanajuato and Aguascalientes. Fusarium culmorum has been repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 6 publications
0
12
0
3
Order By: Relevance
“…Although FBR could also be caused by single Fusarium species (Dugan et al 2003;Stankovic et al 2007;Tirado-Ramírez et al 2018a), a complex of different Fusarium species has been frequently found to be responsible for basal rot in Allium (Delgado-Ortiz et al 2016;Ghanbarzadeh et al 2014), which complicates identification and disease management. In addition, a correct estimation of the importance of each species in the disease complex is not easy.…”
Section: Causal Agents Of Fbrmentioning
confidence: 99%
See 1 more Smart Citation
“…Although FBR could also be caused by single Fusarium species (Dugan et al 2003;Stankovic et al 2007;Tirado-Ramírez et al 2018a), a complex of different Fusarium species has been frequently found to be responsible for basal rot in Allium (Delgado-Ortiz et al 2016;Ghanbarzadeh et al 2014), which complicates identification and disease management. In addition, a correct estimation of the importance of each species in the disease complex is not easy.…”
Section: Causal Agents Of Fbrmentioning
confidence: 99%
“…Even more compounding, the composition of the FBR pathogenic complex appears to vary with geographic regions and plant hosts and is also dynamic within and between growing seasons. For example, a complex of F. oxysporum, F. proliferatum, and F. redolens was responsible for basal rot of onion in Finland (Haapalainen et al 2016), while F. oxysporum, F. proliferatum, F. verticillioides, F. solani, and F. acuminatum were co-associated with basal rot of garlic in North Central Mexico (USA) (Delgado-Ortiz et al 2016). Similarly, while most of the aforementioned species were found in onions, F. acuminatum and F. verticillioides were found only in garlic, and F. culmorum was found only in leek plants with similar symptoms (Table 1).…”
Section: Causal Agents Of Fbrmentioning
confidence: 99%
“…achieved the greatest in vitro growth on F. oxysporum isolated from Capsicum annuum L. Suárez et al (2008) demonstrated that the antagonism of T. harzianum against F. solani, associated with the wilt of Passiflora edulis Sims, at 240 h of confrontation in CD presented inhibition greater than 50 %. This result surpassed some of the treatments evaluated in the present investigation, which could be due to differences in the origin of the (2017) informaron que, T. harzianum cepa A-34 evaluada en este ensayo, alcanzó a las 120 h un 100 % de inhibición del crecimiento micelial del tizón del arroz (Pyricularia grisea Sacc), lo cual se consideró como una acción hiperparásita de esta cepa sobre el fitopatógeno.…”
Section: Resultsmentioning
confidence: 52%
“…Muchas especies tienen una gran capacidad para infectar a las plantas de interés económico y ciertos biotipos pueden causar infecciones oportunistas a los animales y al hombre, atribuidas fundamentalmente por la producción de micotoxinas (Chiotta et al, 2015). Debido a las estructuras de resistencia que posee, denominadas clamidosporas, persisten largos periodos de tiempo en el suelo, lo cual hace inefectiva la alternativa de manejo basada en la rotación de cultivos (Delgado-Ortiz et al, 2016). F. oxysporum es un organismo muy polífago a nivel de especie, se cuantificaron más de 120 formas especiales, las cuales se basan en la infección que produce sobre la planta hospedera.…”
Section: Ceiro-catasúunclassified
See 1 more Smart Citation